2018
DOI: 10.1097/mao.0000000000001691
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter US Clinical Trial With an Electric-Acoustic Stimulation (EAS) System in Adults: Final Outcomes

Abstract: Objective:To demonstrate the safety and effectiveness of the MED-EL Electric-Acoustic Stimulation (EAS) System, for adults with residual low-frequency hearing and severe-to-profound hearing loss in the mid to high frequencies.Study Design:Prospective, repeated measures.Setting:Multicenter, hospital.Patients:Seventy-three subjects implanted with PULSAR or SONATA cochlear implants with FLEX24 electrode arrays.Intervention:Subjects were fit postoperatively with an audio processor, combining electric stimulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 22 publications
7
74
1
2
Order By: Relevance
“…81 Similarly, Pillsbury et al demonstrated hearing preservation using the MED-EL EAS system, reporting that 79% of patients experienced less than 30 dB change in low-frequency hearing, but they reported a much higher continued use of the EAS system at 97% of patients at 1 year follow-up. 82 These findings were in line with previous studies of a similar EAS system in a smaller number of subjects. 83 However, other multicenter studies have shown a less robust preservation rate with hearing preservation electrode arrays, with 66% of patients demonstrating functional low-frequency hearing preservation at 6 months and 54% in another.…”
Section: Hearing Preservation In Cochlear Implantation: Surgical Techsupporting
confidence: 92%
See 1 more Smart Citation
“…81 Similarly, Pillsbury et al demonstrated hearing preservation using the MED-EL EAS system, reporting that 79% of patients experienced less than 30 dB change in low-frequency hearing, but they reported a much higher continued use of the EAS system at 97% of patients at 1 year follow-up. 82 These findings were in line with previous studies of a similar EAS system in a smaller number of subjects. 83 However, other multicenter studies have shown a less robust preservation rate with hearing preservation electrode arrays, with 66% of patients demonstrating functional low-frequency hearing preservation at 6 months and 54% in another.…”
Section: Hearing Preservation In Cochlear Implantation: Surgical Techsupporting
confidence: 92%
“…Additionally, some studies exclude patients shown to have poor long-term outcomes, such as those with older than 65 years and with greater than 30 years of prior deafness and this also should be taken into consideration with the reported hearing preservation rates. 82…”
Section: Hearing Preservation In Cochlear Implantation: Surgical Techmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In 2014, the Nucleus Hybrid L24 cochlear implant (CI) 15 and in 2016, the MED-EL FLEX 20 and 24 CIs 16 were approved by the Food and Drug Administration (FDA) for implantation in those with these indications. In both clinical trials (CTs) 15,16 and in other subsequent research studies, 1,7,10,[13][14][15]17 outcomes demonstrate that by preserving the LF hearing, listeners can utilize fine-timing information 11,18 to aid speech perception in noise and music, 9,11 and maintain localization abilities. [19][20][21][22] Subsequently, the electrically encoded high-frequency information provides important spectral information.…”
Section: Introductionmentioning
confidence: 99%
“…A CI532-es (narancsszínű, tömör átmetszetű) elektródaprofil körülbelül 60%-os relatív keresztmetszet-csökkenése, következményes intracochlearispozíció-változása szembetűnő a korábbi, CI512-es (narancsszínű, szaggatott körvonalú) elektródaprofilhoz képest ESETISMERTETÉS EAS-t alkalmazva a magashang-tartományban károsodott szőrsejtek területét, azaz a basalis régiót sok esetben egy rövid elektródasor bevezetésével fedik le, mellyel megkímélhető az apicalis cochlearis régiók szerkezete, működése. Ez esetben a kihívást a residualis hallás hoszszabb távú megőrzése jelenti [19]. Ha ugyanis a mélyhang-hallásban progresszió következik be, az eredetileg optimális hosszúságú elektróda, fizikai lefedettség hiányában, már nem lesz képes pótolni a cochlea ezen régiójának funkcióját.…”
Section: áBraunclassified